Catastrophic injuries in sports and recreation : causes and prevention : a Canadian study - Tator, Charles H. (University of Toronto Press, 2008)
"Catastrophic Injuries in Sport and Recreation is an essential reference guide to safe participation in a wide variety of sports and recreational activities. A masterful achievement of methodology, it is the first complete epidemiological study and analysis of all catastrophic injuries in all sports and recreational activities that occurred within a large defined geographical area with a large population: ten million people within the province of Ontario between 1986 and 1995. Concentrating on injuries that resulted in death or long term disability, the contributors identify both the personal risk factors for participants and the societal risk factors that are important causes for these kinds of injuries. Providing detailed analysis of 2154 case studies, the contributors demonstrate what went wrong in each event, and show how each injury could have been prevented."--Pub. desc.